The Dynamics of Broadband Markets in Europe : Realizing the 2020 Digital Agenda - Lemstra, Wolter; Melody, William H. (Cambridge : Cambridge University Press, 2014)
The European Commission's Digital Agenda for Europe sets the targets for broadband development by 2020, yet current broadband market outcomes vary widely amongst the EU Member States and the objectives seem challenging for many. In this book, a group of in-country experts follows a framework of qualitative and quantitative analysis to capture patterns, commonalities and differences between twelve different European countries, in terms of infrastructure endowments, institutional arrangements, time of joining the EU, behavior of market actors, personal interventions of regulators, the role of municipalities, and the role perception of governments. By exploring how the past explains present broadband market outcomes, these longitudinal country case studies look to how improvements can be made for the future. As the first in-depth study of broadband developments in Europe, this book will be invaluable to policy-makers, regulators, academic researchers, advisors, and consultants working in the fields of telecommunications, broadband development, technology and innovation.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).